Quel droit de la guerre pour l’OTAN? - Meyrowitz, Henri (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
The debate which has been going on for many years now among governments of the member countries of NATO on the ratification of the Additional Protocol I to the 1949 Geneva Conventions, signed in 1977, focusses mainly on the effects of such an instrument on deterrence and nuclear strategy. It is the fear of these effects that France has used to justify her refusal to become part of Protocol I. At the time of the signing of Protocol I, the US and Great Britain made the declaration that the new regulations as introduced by Protocol I "are not intended to have any effect on and do not regulate or prohibit the use of nuclear weapons". It appears that, for a reason which has nothing to do with atomic weapons, the Reagan administration intends not to ask the Senate for ratification of Protocol I. The governments of Italy and Belgium who ratified the Protocol in February and May 1986 respectively, have supplemented their ratification with a declaration similar to that of the two powers. As for the legality of the use of nuclear weapons, the answer must from now on rely on the combination of Protocol I and the "nuclear clause" from the declaration of the two powers and their allies. Hence the status of nuclear weapons in international law is comprised of three elements : a) The first use of nuclear weapons is not, in itself prohibited. - b) This use is subjected to the regulations of the common law of war, as has been "reaffirmed" by Protocol I, and which applies both to conventional and nuclear weapons. - c) The bans and restrictions, as provided for in these regulations, and which mark out the thin bounds which allow for the use of atomic weapons, pertain only to the use of these arms and not to nuclear deterrence.